Global trends in BRCA-related breast cancer research from 2013 to 2022: A scientometric analysis - Huang, Yujie; Zheng, Daitian; Yang, Qiuping; Wu, Jinyao; Tian, Huiting; Ji, Zeqi; Chen, Lingzhi; Cai, Jiehui; Li, Zhiyang; Chen, Yexi (Frontiers in Oncology, 2023)
Introduction: Since the mid-2000s, breast cancer incidence among women has slowly increased at about 0.5% per year. In the last three decades, Breast Cancer Susceptibility Gene (BRCA) has been proven to be the crucial gene in encouraging the incidence and development of breast cancer.However, scientometric analysis on BRCA-related breast cancer is in shortage. Thus, to have a clear understanding of the current status and catch up with the hotspots, a scientometric analysis was conducted on specific academic publications collected from the Web of Science (WoS).We searched the Web of Science Core Collection (WoSCC) to procure associated articles as our dataset. Bibliometric, CiteSpace, VOSviewer, and HistCite software were then applied to conduct visual analyses of countries, institutions, journals, authors, landmark articles, and keywords in this research field.Results: A total of 7,266 articles and 1,310 review articles published between 2013 to 2022 were retrieved eventually. The annual output steadily rose year by year and peaked in 2021. The USA led the way in the number of published works, total citations, and collaboration.Breast Cancer Research and Treatment was the most favoured journal in this research field. Narod SA from the University of Toronto produced the most publications. At last, the most prominent keywords were "breast cancer" (n=1,778), "women" (n=1,369), "brca1" (n=1,276), "ovarian cancer" (n=1,259), "risk" (n=1,181), and "mutations" (n=929), which exposed the hotspots within the BRCA domain of breast cancer study.The tendency in the BRCA research field over the past decade was presented by the scientometric analysis. The current research focus is the clinical trials of poly-adenosine diphosphate ribose polymerase inhibitors (PARPi) drugs and their resistance mechanisms.